Business analysis enlargement common carp (cyprinus carpio) floating net cages in tanjung alai village xiii koto kampar district riau province - Angga Priyetno; Hendrik '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 8th until 16th May 2013. The method used in this study is the case study method to 2 farmers who each seek 10 units and 15 units floating net cages (FNC). This study aims to determine the cost and feasibility of investment business in the FNC enlargement common carp in Tanjung Alai village.The results of this study indicate if FNC businesses in Tanjung Alai village worth the investment cost of Rp. 361.781.000 to 10 units cages and Rp.514.485.000 to 15 units cages. The investment criteria such as NPV obtained for Rp.996.602.000 to 10 units cages and Rp.1.630.990.000 to 15 units cages, for ten years. Then, BCR of 1,23 to 10 units cages and 1,26 to 15 units cages. As well, IRR value of more than 40%.The overall investment value of the business to meet the eligibility criteria were developed.Keywords: floating net cages (FNC), investment, NPV, BCR, IRR